CUSTOMER BEHAVIOR DAN DIGITAL MARKETING TERHADAP PURCHASE INTENTION - Dedi, selmi; Kholimatul, Sahdiah; Bopeng, Louis Soemadi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2024)
This study aims to examine Customer Behavior and Digital Marketing at Keripik Raos located in Manokwari Regency. This type of research is quantitative using primary and secondary data. The research subject is the owner of Keripik Raos, while the object of research is Keripik Raos consumers who are involved in the application of Customer Behavior and Digital Marketing. This study uses multiple linear regression methods on 120 respondents who are consumers of Keripik Raos to measure the effect of Customer Behavior and Digital Marketing on Purchase Intention. The data collection techniques used include observation, interviews, and questionnaires. The results showed that Keripik Raos has successfully implemented Customer Behavior and Digital Marketing to increase Purchase Intention. The benefits of Customer Behavior and Digital Marketing strategies include focusing more on consumers and reaching consumers through social media, so that the products offered by Keripik Raos match consumer needs. However, Keripik Roas faces several obstacles in implementing this strategy, namely not setting positioing, financial limitations, lack of skills in design, photography, and editing, and not having employees who are experts in marketing.